(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Thyroid hormones have been shown to promote the generation of reactive oxygen species (ROS), consumption of antioxidants, and induction of oxidative stress, which triggers the release of heat shock proteins (HSPs) and VEGF-dependent angiogenesis. The present study investigated the effect of altered thyroid states, hypothyroidism and hyperthyroidism on hepatic and renal functions, oxidative stress biomarkers, and hepatorenal expressions of HSP70, HSP90, and VEGF. Male Wistar rats were randomized into vehicle-treated control, carbimazole-induced hypothyroidism, or levothyroxine-induced hyperthyroidism. Altered thyroid states caused impaired hepatic and renal functions accompanied by elevated malondialdehyde and reduced glutathione content and superoxide dismutase and catalase activities in the hepatic and renal tissues. These derangements were associated with down-regulation of hepatic and renal HSP70 and HSP90 and upregulation of hepatic and renal VEGF expression. Findings of histopathological examinations of the hepatic and renal tissues align with the biochemical derangements observed. This study reveals that dysthyroidism impairs hepatorenal function via induction of oxidative stress and modulation of HSP70/HSP90/VEGF signaling